Implementation of Center-Based Games to Improve Early Childhood Cognitive Abilities - Gusnawati Honjong (Pt. Anagata Sembagi Education, 2025)
This study aims to determine the effectiveness of implementing center-based games in improving the cognitive abilities of early childhood. This study used the Classroom Action Research (CAR) method with the Kemmis & McTaggart model which was implemented in two cycles. The subjects were 15 children in group B aged 5-6 years in one of the PAUD in Mamuju City. Data collection techniques were carried out through observation, interviews, documentation, and simple cognitive tests. The results showed that the implementation of center-based games, such as block centers, natural materials, art, and role-playing, was able to improve children's cognitive abilities. There was an increase in the average cognitive achievement of children from 65% in cycle I to 85% in cycle II. In addition, children demonstrated better logical thinking, problem-solving, and understanding of basic mathematical concepts. This study concluded that center-based games are effective in optimizing the cognitive development of early childhood.